HOW TO FOSTER EMPLOYEE PERFORMANCE? THE ROLE OF ORGANIZATIONAL CULTURE AND WORK ETHOS WITH MOTIVATION AS INTERVENING VARIABLES - Setiabudi Setiabudi; Rosana Eri Puspita; Mochlasin Mochlasin (Ultima Management : Jurnal Ilmu Manajemen, 2021)
Abstract - Employee performance of Bank Syariah Indonesia (BSI) after the merger is an important thing to study because the three banks that are the origin of these banks have different work cultures. This study analyses organizational culture and works ethic on employee performance through work motivation as an intervening variable. The data collection method was carried out by distributing questionnaires to Bank Syariah Indonesia (BSI)employees in the Semarang office branch. The sample used was 41 respondents with a saturated sample technique. The data obtained were then processed using SPSS. The data analysis was used as path analysis. This study showed that organizational culture has a positive and not significant effect on employee performance. Work ethic has a positive and significant effect on employee performance and works motivation. Organizational culture positively and significantly affects work motivation. Work motivation has a positive and significant effect on work motivation and employee performance. Other results showed that work motivation mediates organizational culture's influence on employee performance, and work motivation mediates the effect of work ethic on employee performance. This research is expected to be additional material for banks to improve quality in terms of employee performance. It is excellent, and it must be even better, based on this research in the future. Keywords: Employee Performance; Organisational Culture; Work Ethic; Work Motivation